2010
DOI: 10.1287/inte.1090.0476
|View full text |Cite
|
Sign up to set email alerts
|

HP Transforms Product Portfolio Management with Operations Research

Abstract: cost analysis; stochastic inventory analysis; flow algorithms; product portfolio management; inventory management; regression; statistic; binary programming; Lagrangian relaxation; parametric maximum flow HP offers many innovative products to meet diverse customer needs. The breadth of its product offerings has helped the company achieve unparalleled market reach; however, it has come with significant costs and challenges. By offering multiple similar products, a manufacturer increases its overall demand volat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…In contrast to our approach that seeks to maximize profits using our empirical cost of complexity function, they maximize revenue with greedy heuristics and demonstrate their approach, using two examples-snack cakes and tires-their recommendations for tires leads to a 5.8% revenue increase. Ward et al (2010) develops two analytical tools to apply to Hewlett-Packard's product line problem. Like CAT, HP has product lines that could, in theory, span millions of different configurations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast to our approach that seeks to maximize profits using our empirical cost of complexity function, they maximize revenue with greedy heuristics and demonstrate their approach, using two examples-snack cakes and tires-their recommendations for tires leads to a 5.8% revenue increase. Ward et al (2010) develops two analytical tools to apply to Hewlett-Packard's product line problem. Like CAT, HP has product lines that could, in theory, span millions of different configurations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, they show just two examples -snack cakes and tires -implementing a small set of their recommended changes with the tires line, increasing revenue by 5.8%. Ward et al (2010) is another recent paper that rigorously applies an analytical framework to the product line problem, developing two tools to help Hewlett-Packard. Like Caterpillar, HP has product lines that could, in theory, span millions of different configurations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, for some classes of parametric min‐cut problems, where only some capacities may vary, it was shown that there exists a selection of minimum cuts which is monotone (with respect to set inclusion) in the parameter λ . This result was used to design efficient algorithms to solve the corresponding parametric max‐flow problem (see, e.g., , and references therein).…”
Section: Introductionmentioning
confidence: 99%